BRAINLIEST TO WHOEVER GETS IT RIGHT
Which of the following accurately shows the first step when solving the following system of equations by substitution?
f(x) = -4x^2 + 3x + 1
g(x) = -6x +5
a -4x^2+ 3x + 1 = -6x +5
b 4x^2 + 3x +1 - 6x + 5 = 0
c g(x)= -6(-4x^2 + 3x + 1) + 5
df() = -4(-6x + 5)^2 +3(-6x + 5) +1

Respuesta :

Answer:

c and d

Step-by-step explanation:

because

- In f(x),evey time you find  X you write(-6x+5) instead

4x²-----------4(-6x+5)²

3x+1------------3(-6x+5) +1

-In g(x),evey time you find  X you write(-4x² +3x+1)  instead